2009
DOI: 10.1111/j.1540-627x.2009.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

The Deal Structuring Stage of the Venture Capitalist Decision-Making Process: Exploring Confidence and Control

Abstract: This exploratory study examines the deal structuring stage of the venture capitalist decision-making process. Here, the primary issues of concern are investor confidence and potential control of a venture in relation to the level of financing the investor provides and the structure with which the funding is delivered. Confidence comes in support of the entrepreneur, the venture itself, or a combination of the two, prior to capital transfer, but after the initial "invest or not invest" decision has already occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 81 publications
1
25
0
4
Order By: Relevance
“…Relevant actors (henceforth 'deal-makers') include innovators, investors and financiers, and professional intermediaries such as lawyers and technology transfer officers (Uzzi, 1999;Vohora et al, 2004;Payne et al, 2009). In this paper, our focus is on deal-making as a social process (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant actors (henceforth 'deal-makers') include innovators, investors and financiers, and professional intermediaries such as lawyers and technology transfer officers (Uzzi, 1999;Vohora et al, 2004;Payne et al, 2009). In this paper, our focus is on deal-making as a social process (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the great majority of previous studies have addressed this role in the context of the stronger, dyadic ties of the later phases of the dealmaking process (e.g. Liao and Welsch, 2005;Tyebjee & Bruno, 1984;Payne et al, 2009;Larson, 1992), and especially the collaborative and monitoring relationships post-investment (e.g. Harrison et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…That is, while angels do invest with an expectation of economic returns, they also invest based on perceptions and for behavioral reasons. Studies have found several factors that act as signals that can influence their decision making, such as characteristics of the entrepreneurial firm or its product (Clark, 2008;Payne et al, 2009), of the entrepreneur (Mason & Stark, 2004;Prasad, Bruton, & Vozikis, 2000), or of the angel investor (van Osnabrugge, 1998;Wong & Ho, 2007), or any number of other criteria of importance to the investing angel.…”
Section: The Decision To Invest: What We Knowmentioning
confidence: 99%
“…Perceptions of higher quality products or greater product uniqueness impact angel investor decision making (Payne et al, 2009;Sudek, 2006Sudek, /2007, as does the attractiveness of the market or the environment in which the venture operates (Mason & Harrison, 1996;Payne et al, 2009;Payne & McCarty, 2002). Readiness for funding, indicated by the characteristics of the management team, intellectual property, or the product's stage of development, also affect angel investor funding decisions (Brush, Edelman, & Manolova, 2012).…”
Section: The Decision To Invest: What We Knowmentioning
confidence: 99%
“…Pour neutraliser ces coûts, les mécanismes de gouvernance, notamment le conseil d'administration, sont mobilisés (Filatotchev, Wright et Arberk, 2006). Les principaux critères d'investissement des SCR concernent les caractéristiques de l'entrepreneur (Zutshi et al, 1999), d'une part, son idée d'affaires (Silva, 2004), la confiance qu'il inspire (Payne et al, 2009) ). Enfin, les projections financières ne semblent pas être systématiquement un critère de sélection (Mason et Stark, 2004 ;Silva, 2004).…”
Section: Le Financement Par Capital-risque (Cr)unclassified